Children's rights and commercial communication in the digital era : towards an empowering regulatory framework for commercial communication / Valerie Verdoodt. - Verdoodt, Valerie (Intersentia, 2020)
On 20 November 2019 the United Nations Convention on the Rights of the Child celebrates its 30th anniversary. In 1989, when the Convention was adopted, children came across advertising on television, on billboards in the street, in shops and through leaflets in their mailbox. Over the past 30 years, the way in which children are targeted by advertisers and the formats that are used have changed significantly. Think of advergames, influencer marketing, and behavioural targeted advertising. The specific features of these formats, such as their immersive, interactive and personalised nature, make it difficult for children to understand the commercial and persuasive intent of the commercial messages directed at them. This book presents an original and timely fundamental rethinking of the regulatory framework of commercial communication from a children's rights perspective. Offering a carefully considered, well-documented overview and in-depth evaluation of several legislative frameworks, policy documents, self- and co-regulatory initiatives and literature from a variety of disciplines, it works towards the development of children's rights-inspired recommendations for an empowering regulatory framework for online commercial communication aimed at children. It is a subject with great societal relevance which contributes to the further realisation of children's rights in the digital environment. Valerie Verdoodt is a fellow in law at the London School of Economics. Her research focuses on the legal and fundamental rights questions originating from the development of new media and technology, in particular regarding the protection and participation of children online. She also teaches Information technology and the law, Cyberlaw and EU Law on the LSE law programme.